Digital Marketing and Outdoor Advertising in Smart Cities - Nikola VANGELOV (Smart Cities and Regional Development Journal)
The paper focuses on analyzing the key aspects digital marketing, outdoor advertising and smart cities. It studies the foundations traditional marketing - the establishment of its theoretical framework and its development throughout the years. The articles aims at finding out what is the crossing point between digital outdoor advertising, urban areas and smart cities residents. It puts main focus on the promotional part of the mix and analyzes the new approaches in terms of using online channels. Through content analysis the main aspects of digital marketing, smart cities and outdoor advertising are being studied – the development of the definition of marketing; what digital is; the difference between digital and online; what the new opportunities before marketers in using online channels are, as part of the digital ones. The paper suggests an additional component of smart cities – interactivity. It sets examples from outdoor traditional advertising and digital advertising that is placed on cities’ billboards, buildings and public transport with main focus on interactivity.